Analysis of Historical Trends and Recent Elimination of Malaria from Sri Lanka and Its Applicability for Malaria Control in Other Countries - Wijesundere, Dilkushi Anula; Ramasamy, Ranjan (Frontiers in Public Health, 2017)
Sri Lanka is a tropical island located South of India in the Indian Ocean. Malaria has been prevalent in the island for centuries but the country succeeded in eliminating the disease in 2013. Factors governing the past endemicity of malaria and its successful elimination from Sri Lanka in 2013 are analyzed. There is evidence that malaria might have been first introduced in the thirteenth century into a dry zone area with extensive irrigation works. Regular widespread epidemics of the disease have been documented in the twentieth century. The island nature of Sri Lanka, generally low transmission rates, widespread and accessible government hospitals and clinics that provide free and readily available diagnosis and treatment for malaria, adequate financial support and commitment to the Antimalaria Campaign (AMC), national and decentralized malaria control efforts sustained over a long period by dedicated and competent AMC staff, and the absence of zoonotic malaria are recognized as key factors responsible for eliminating malaria from Sri Lanka. These factors are analyzed in the context of their relevance to the present malaria elimination efforts in other countries with the overall aim of globally eradicating the disease.